2016
DOI: 10.1245/s10434-015-5077-z
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life After Pancreatectomy: Results From a Randomized Controlled Trial

Abstract: Background A recent prospective randomized trial demonstrated that prophylactic pasireotide reduces the incidence of pancreatic complications (PC) following resection. In this secondary analysis, we aimed to describe quality of life (QoL) before and after resection, characterize the impact of PC on QoL, and assess whether pasireotide improves QoL. Methods We conducted a randomized, double-blind, placebo-controlled trial of preoperative pasireotide in patients undergoing pancreatectomy. Participants completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 15 publications
0
51
2
3
Order By: Relevance
“…For example, Heerkens et al found that health-related QOL decreased considerably immediately after pancreatectomy for malignancy, but near full recovery occurred 3-6 months postoperatively [9]. Similarly, Eaton et al utilized data from the prospective randomized controlled trial of prophylactic pasireotide to show that while significant declines in QOL occurred immediately postoperatively, most symptoms abated and emotional function improved by 60 days after pancreatectomy [5].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
“…For example, Heerkens et al found that health-related QOL decreased considerably immediately after pancreatectomy for malignancy, but near full recovery occurred 3-6 months postoperatively [9]. Similarly, Eaton et al utilized data from the prospective randomized controlled trial of prophylactic pasireotide to show that while significant declines in QOL occurred immediately postoperatively, most symptoms abated and emotional function improved by 60 days after pancreatectomy [5].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
“…Previous studies have shown that in the period 1-3 months after major pancreatic operations, there is an obvious decrease in QoL. [3][4][5][6] It takes 3-6 months for QoL to fully recover after surgery. 3,[5][6][7] Literature has reported negative effects of complications on QoL in oesophageal and (colo)rectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Previous studies evaluating the difference in QoL between patients with and without complications demonstrate conflicting results. 4,6,[18][19][20] Some studies suggest there are no significant differences in postoperative QoL between patients with or without complications, 6,20 while others show that complications tend to negatively affect postoperative QoL. 4,18,19 Most patients in these studies were part of large randomized clinical trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient‐reported outcome measures (PROMs) have become a growing focus in oncology. RCTs demonstrated improvements in patient engagement, outcome and satisfaction with use of PROMs, which led to their routine use in clinical practice.…”
Section: Introductionmentioning
confidence: 99%